A prospective observational study on etiology and management influencing outcome in operatively managed cases of acute intestinal obstruction in adults - Dipan Mukhopadhyay,; Anupam Banerjee,; Subhadeep Datta,; Partha Sarathi Dutta, (Asian Journal of Medical Sciences, 2023)
Background: Acute intestinal obstruction (IO) is an important cause for acute abdomen in surgery which presents as abdominal pain, vomiting, distension, and constipation depending on the level and extent of obstruction of gastrointestinal tract. Early diagnosis of acute IO with understanding of various etiologies, use of better diagnostic techniques, and skillful operative management and good postoperative care, carries a good outcome. Aims and Objectives: The objective of the study was to find out the prevalence of various etiologies of acute IO and to study the various post-operative morbidity and mortality. Materials and Methods: This was a hospital-based observational study in the Department of General Surgery of Calcutta National Medical College and Hospital among patients with a diagnosis of acute IO during the study period of December 2016-April 2018. Results: Acute IO commonly affects male with a male: female ratio 7:3 and the most common occurrence in the age group of 40–59 years (30%). The most common etiology was obstructed/strangulated hernia (36%), followed by large bowel neoplasm (18%), adhesion (16%), intestinal tuberculosis (12%), and volvulus (10%). The most common surgical procedure performed was the resection of gangrenous bowel and creation of stoma (30%), followed by prosthetic repair of hernia (28%). The mortality rate of the present study was 12%. The morbidity rate was 46%attributing mainly to respiratory complications (30.4%) and surgical site infections (26.08%). Conclusion: This study demonstrates that the pattern of IO differs from the Western world with obstructed hernias being the most important cause and also emphasizes the fact that intestinal tuberculosis assumes a prominent role.